Efficacy of polyethylene glycol loxenatide for type 2 diabetes mellitus patients: a systematic review and meta-analysis - Liu, Yibo; Ma, Wenjing; Fu, Hui; Zhang, Zhe; Yin, Yanyan; Wang, Yongchun; Liu, Wei; Yu, Shaohong; Zhang, Zhongwen (Frontiers in Pharmacology, 2024)
Objective: Some studies have proved that polyethylene glycol loxenatide (PEG-Loxe) has significant effects on controlling blood glucose and body weight in patients with type 2 diabetes mellitus (T2DM), but there is still some controversy over the improvement of blood lipid profiles (BLP) and blood pressure (BP), and more evidences are needed to verify such effects. Therefore, this study was conducted to provide a comprehensive evaluation of the efficacy of PEG-Loxe in improving blood glucose (BG), BLP, BP, body mass index (BMI), and body weight (BW) in patients with T2DM for clinical reference. Methods: Randomized controlled trials (RCT) in which PEG-Loxe was applied to treat T2DM were retrieved by searching PubMed, Cochrane Library, Embase, Medline, Scopus, Web of Science, China National Knowledge Infrastructure, China Scientific Journal, Wanfang Data, and SinoMed databases. Outcome measures included BG, BLP, BP, BMI, and BW. RevMan 5.3 software was used to perform data analysis. Results: Eighteen trials were identified involving 2166 patients. In experimental group 1260 patients received PEG-Loxe alone or with other hypoglycemic agents, while in control group 906 patients received placebo or other hypoglycemic agents. In the overall analysis, PEG-Loxe significantly reduced the levels of glycosylated hemoglobin (HbA1c), fasting plasma glucose (FPG), 2-hour postprandial blood glucose (2-h PBG), BMI, and BW compared with control group. However, it had no obvious effect on total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), systolic blood pressure (SBP), and diastolic blood pressure (DBP).PEG-Loxe has better hypoglycemic effects compared with placebo in patients with T2DM, but could not significantly improved TG, LDL-C, HDL-C, SBP, and DBP. And the combination of conventional hypoglycemic drugs (CHD) and PEG-Loxe could more effectively improve the levels of HbA1c, FPG, 2-h PBG, TC, TG, BMI, and BW compared with CHD in T2DM patients.